The outcome of loop electrosurgical excision procedure following treatment of cervical intra-epithelial neoplasia 2 and 3 - M. Rokeya Satter; M. Tozammel Hoque; M. Mozammel Hoque; M. Saidur Rahman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: In Bangladesh, loop electrosurgical excision procedure (LEEP) is an ongoing program of government health service for the management of cervical intra-epithelial neoplasia (CIN) 2 and 3. The aim of this study was to evaluate the outcome of loop electrosurgical excision procedure following treatment of cervical intra-epithelial neoplasia 2 and 3. Methods: This descriptive cross-sectional study was conducted in outpatient department (OPD), gynaecology and obstetrics department, Rangpur Medical College Hospital, Rangpur, Bangladesh during the period from July 2011 to June 2012. In total 75 patients, underwent LEEP following treatment of CIN 2 and 3 were selected for this study as study subjects. Data analysis was done by using statistical package for social science (SPSS) 16 version. Results: In this study, majority of the participants were from 30-39 years’ age group which was 57%. Besides this 23%, 19% and 1% patients were from <30, 40-49 and ≥50 age groups respectively. The mean parity of the patients was 3.68 with standard deviation of ±1.31 and range was 1 to 7. In analyzing the parity of the participants, we observed that, in 47% and 24% patients the party were 2 and 3 respectively which were noticeable. Besides these in 11%, 8%, 7%, 1% and 3% cases the parity were found as 1, 4, 5, 6 and 7 respectively. In analyzing the histopathology among patients, we found, 76% cases were with CIN-1 whereas the rest 24% cases were with CIN-2. Conclusions: Cervical cancer is the most common malignancy and a major cause of cancer death among Bangladeshi women. This may be due to lack of awareness, scarce of screening facility, poverty and illiteracy. The LEEP procedure has many advantages including high success rate, low cost and ease of use.